Keterampilan Guru dalam Mengelola Kelas pada Pembelajaran Siswa Kelas IV SDV 55/I Sridadi - Elsa Nadia Rani; Framesti Putri intan Kusuma; Riska Dwi Rahma Putri; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
This study aims to determine the skills of teachers in managing the classroom. This type of research is qualitative as a research procedure that produces descriptive data in the form of written and spoken words from the behavior of the people observed. The subject of this research is the fourth grade teacher at SDN 55/I Sridadi. The results of this study indicate that the teacher's skills in managing the classroom can be done by always getting students to always be disciplined, neat and clean in everything. Classrooms with various decorations so that the class feels comfortable and beautiful. Always make lesson plans for one semester. Using learning resources from books and the internet and several learning media according to the learning material. And have good skills in opening and closing lessons, explaining learning materials, providing reinforcement and guiding group discussions.